Response of Mirasol chili pepper to reduced tillage, soil amendments and plastic mulch - Amador-Ramírez, Mario Domingo; Velásquez-Valle, Rodolfo; Sánchez-Toledano, Blanca Isabel; Acosta-Díaz, Efraín (Revista Mexicana de Ciencias Agrícolas, 2018)
The interest in the sustainability of some systems of dried chili pepper (Capsicum annuum L.) comes from the intensive production to which this crop is subjected to, caused by the excessive use of agricultural activities. The aim of this study was to: 1) evaluate the effects of reduced tillage, green manure incorporation, incorporation of dry manure and the association drip irrigation + plastic mulch, on the growth and yield of dried chili peppers, comparing these effects with those of the conventional production system; and 2) estimate the economic benefits of the management systems mentioned above. The chili pepper plants stopped their growth in terms of height around 960 and 989 HU, while in terms of stem diameter the chili pepper plants stopped growing between 972 and 980 HU. The yield of premium chili peppers with LR was constant between years. The yield response to management systems different to the LR was inconsistent between years due to the susceptibility of the crop to external factors such as environmental factors and diseases. The benefit/cost relationship through the years shown by the LR system was constant, compared to ACOL and IAS, which showed losses and gains.
Keywords: economic analysis; heat units; nonlinear regression; vegetative growth